Vanilla extract intervention on neonatal pain and comfort levels during venous blood sampling - Ilmiasih, Reni; Juwitasari, Juwitasari (Jurnal Keperawatan, 2023)
Introduction: Venous blood sampling is always uncomfortable and painful. Especially for neonates. Several impacts, such as rapid pulse, tissue damage, psychological stress, and altered behavior. Improper intervention results in further complications like hyperalgesia and severe pain experience. Objectives: Identify the effects of vanilla extract on neonatal pain and comfort levels of neonates during venous blood sampling. Methods: Within three months of data collection in a private hospital, the quasi-experiment post-test-only with a control group design used quota sampling with 40 neonates. The Neonatal Infant Pain Scale (NIPS) is used to assess the pain level in newborns, and the Comfort Scale is used to assess their comfort level. Results: More than half of neonates (64%) were 24 hours old, and 60 % were boys. As many as 76% of them were diagnosed with umbilical cord infection, PROM, Etc. There was no significant difference in the pain scales of the two groups (p=0.51), but there was a significant difference in the results of the comfort level (p= 0.00). These results follow previous research that found that the vanilla concentrations of 0.64% and 2% could not significantly reduce pain. Conclusions: The nerve response of neonates has not developed correctly, or the asphyxia problem during the intervention, resulting in the smell of vanilla aromatherapy 0.64% applied not being able to overcome pain significantly. It is further recommended to vary the dose to see the impact of pain.